Diversity and Antimicrobial Activity of Lichens-Associated Actinomycetes in Cibinong Science Centre (CSC) and Cibodas Botanical Garden (CBG) Indonesia - Susanti, Agustina Eko; Ratnakomala, Shanti; Mangunwardoyo, Wibowo; Lisdiyanti, Puspita (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2019)
Bioprospecting has developed to all biological taxa including procaryotic. Actinomycetes become interesting procaryotic because of the ability to produce important secondary metabolite for human life. Actinomycetes are known as the largest antibiotic producer that has a broad range habitat. Some research has been done to find new antibiotic from the various habitat of actinomycetes. One of the interesting habitats of actinomycetes which never been explored in Indonesia is lichens... Lichens as the symbiotic structure of alga and fungi areknown as the ecological niche of various kinds of microorganisms including actinomycetes. Cibinong Science Centre (CSC) and Cibodas Botanical Garden (CBG) have various species of trees as the habitat of lichens. These areas are known as one of the research locations to explore the biodiversity of Indonesia. The aims of this research is to study the diversity and antimicrobial potency of actinomycetes isolated from 10 lichen samples with various type of thallus; crustose, fructose and foliose. Lichen samples were grown on the bark of 9 trees species in CSC and CBG. Isolation process used three agar media; HV, YIM6 and YIM711 with cycloheximide and nalidixic acid. Molecular identification based on 16S rRNA gene sequence. Antimicrobial activity was tested to 65 isolates by agar diffusion method to Bacillus subtilis BTCC B.612, Escherichia coli BTCC B.614, Candida albicans BTCC Y.33, Staphylococcus aureus BTCC B.611, Micrococcus luteus BTCC B.552. Isolation process retrieved 125 isolates with the highest number grow on HV agar medium. Based on the sample, the highest number of actinomycetes were isolated from crustose lichen attached on the bark of Averrhoea carambola. A total 69 isolates were identified as the genera Actinoplanes, Amycolatopsis, Angustibacter, Kribbella, Micromonospora, Mycobacterium, and Streptomyces. The screening process showed 24 isolates have antimicrobial activity, with the highest inhibitory activity against Micrococcus luteus BTCC B.552.